Pengaruh Komite Audit, Dewan Komisaris Independen Dan Kepemilikan Intitusional Terhadap Nilai Perusahaan Sektor Makanan Dan Minuman (Studi Empiris Pada Perusahaan Manufaktur SUB Sektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Tahun 2019-2022) - Syalsabila Putri; Rahmaita (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2024)
This research aims to determine the influence of the audit committee, independent board of commissioners and institutional ownership on company value. This type of research is correlational research, with a quantitative approach. This research uses secondary data taken from the BEI data website. The sample used was 68 food and beverage sector companies over a 4 year observation period. The sampling technique was carried out using the purposive sampling method. The analytical method used is multiple linear regression analysis with analysis tools using SPSS 21. The results of this research show that the audit committee variable has a negative and significant effect on company value, the independent board of commissioners variable has a positive and significant effect on company value, the institutional ownership variable has no significant effect on the value of the company.